1993
DOI: 10.1007/bf01067434
|View full text |Cite
|
Sign up to set email alerts
|

Is the gender difference in mental rotation disappearing?

Abstract: Several investigators have used meta-analysis to compare the results of studies of gender differences on various spatial tests and have concluded that the magnitude of the gender difference in spatial ability is decreasing over time. The present study used meta-analytic techniques to compare the effect size (d) of the gender difference in 14 studies published from 1975 to 1992 which administered the Mental Rotations test to adolescents and young adults. Males scored significantly higher than females in all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
144
2
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(168 citation statements)
references
References 31 publications
16
144
2
6
Order By: Relevance
“…In the visuospatial domain, one study (Lejbak et al 2011) observed that men outperformed women in the n-back task. This finding agrees with several studies that have reported that men are superior to women in diverse visuospatial tasks (for meta-analytic studies see Masters and Sanders 1993;Voyer et al 1995). Sex differences in these studies were only examined in young adults; thus, the possibility of a steadier pattern of working memory across adulthood remains unexplored with the n-back task.…”
Section: Introductionsupporting
confidence: 80%
“…In the visuospatial domain, one study (Lejbak et al 2011) observed that men outperformed women in the n-back task. This finding agrees with several studies that have reported that men are superior to women in diverse visuospatial tasks (for meta-analytic studies see Masters and Sanders 1993;Voyer et al 1995). Sex differences in these studies were only examined in young adults; thus, the possibility of a steadier pattern of working memory across adulthood remains unexplored with the n-back task.…”
Section: Introductionsupporting
confidence: 80%
“…Experiment 1 results did not replicate the commonly reported sex finding with men outperforming women in rotation rate while men were still more accurate than women. Thus, our findings relating to performance on mental rotation did show a sex difference, but this difference was not as robust as the literature suggests (Collins & Kimura, 1997;Linn & Petersen, 1985;Masters & Sanders, 1993;Voyer et al, 1995). The idea of other individual differences contributing to the difference in mental rotation performance becomes more important.…”
Section: Discussioncontrasting
confidence: 38%
“…Not uncommonly, men mentally rotate faster than women (Linn & Petersen, 1985;Lippa, Collaer, & Peters, 2010;Maccoby & Jacklin, 1974;Masters & Sanders, 1993;Peters, 2005;Resnick, 1993;Richardson, 1994;Voyer, Voyer, & Bryden, 1995) although accuracy is often comparable (Goldstein, Haldane, & Mitchell, 1990;Kail et al, 1979;Voyer & Bryden, 1990). In reality this male advantage may be more ethereal.…”
Section: Mental Rotation Taskmentioning
confidence: 99%
“…In addition, it is important to include the effects of the students' innate abilities in spatial assignments (Guillot et al; Hegarty et al; Khot et al) given that generic differences have been observed between men and women in which men obtain higher scores in mental rotation tasks (Masters & Sanders, 1993).…”
Section: Discussionmentioning
confidence: 99%